In situ synthesis of Pt nanoparticles in SBA-15 by encapsulating in modified template micelles: size restricted growth within the mesochannels - Prashar, Atul K.; Hodgkins, Robert P.; Kumar, Rajiv; Devi, R. Nandini (Journal of Materials Chemistry, 2008)
A truly in situ and simple method is developed for nanoparticle incorporation within the mesochannels of SBA-15 involving dispersion of metal precursors in surfactant-modified polymer micelles. The diffusion of the precursor within the micellar structure is aided by interaction with the cationic head group of the surfactant leading to a unique method to facilitate the formation of highly disperse, uniform nanoparticles molded by the walls of the mesochannels. The nanoparticle incorporated mesoporous material has a highly enhanced surface area and adsorption capabilities in comparison to its parent materials without any pore blockage which makes this method ideal for the preparation of nanocatalysts.

In situ encapsulation of pt nanoarchitectures of varying morphologies in mesoporous compounds - Prashar, Atul K.; Hodgkins, Robert P.; Chandran, Jima N.; Rajamohanan, P. R.; Devi, R. Nandini (Chemistry of Materials, 2010)
Nanoparticle morphology could be engineered and fine-tuned based on a novel in situ template method Different shapes of platinum nanoparticles were obtained from very low concentrations of precursors and could be isolated exclusively inside the mesochannels of SBA-15 This was achieved by dispersing a platinum precursor in surfactant modified polymer to different extents and using these composite materials as templates for the formation of mesoporous silica [PtCl(6)](2-) interacts with the cationic headgroup of the surfactant and facilitates the isolation of precursors within the composite template leading to the formation of nanoparticles molded by the walls of the mesochannels when calcined When this [PtCl(6)](2-)-surfactant-polymer micelle composite is aged for different duration, Pt nanoparticles of various morphologies like spheroids, nano rugby balls, and nanorods are obtained